2018
DOI: 10.1074/jbc.ra117.000773
|View full text |Cite
|
Sign up to set email alerts
|

CLOCK phosphorylation by AKT regulates its nuclear accumulation and circadian gene expression in peripheral tissues

Abstract: ircadian ocomotorutput yclesaput (CLOCK) is a transcription factor that activates transcription of clock-controlled genes by heterodimerizing with BMAL1 and binding to E-box elements on DNA. Although several phosphorylation sites on CLOCK have already been identified, this study characterizes a novel phosphorylation site at serine 845 (Ser-836 in humans). Here, we show that CLOCK is a novel AKT substrate and in cells, and this phosphorylation site is a negative regulator of CLOCK nuclear localization by acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…This would occur via phosphorylating CLOCK (Ser 845 ) and ARNTL (Ser 42 ), which subsequently influences their nuclear/cytoplasmic shuttling. 75,76 In the present study, the lack of statistical changes in ARNTL protein abundance due to AA treatments was inconsistent with previous work where AKT deficiency decreased ARNTL abundance. 77 Lower p-AKT protein with increased supply of Arg could alleviate inhibition on clock function, but the opposite response of CLOCK protein abundance with increased Met or Arg alone or in combination might have occurred because AKT might not be the sole regulator of CLOCK and ARNTL in mammary cells.…”
Section: Circadian Clock Networkcontrasting
confidence: 99%
“…This would occur via phosphorylating CLOCK (Ser 845 ) and ARNTL (Ser 42 ), which subsequently influences their nuclear/cytoplasmic shuttling. 75,76 In the present study, the lack of statistical changes in ARNTL protein abundance due to AA treatments was inconsistent with previous work where AKT deficiency decreased ARNTL abundance. 77 Lower p-AKT protein with increased supply of Arg could alleviate inhibition on clock function, but the opposite response of CLOCK protein abundance with increased Met or Arg alone or in combination might have occurred because AKT might not be the sole regulator of CLOCK and ARNTL in mammary cells.…”
Section: Circadian Clock Networkcontrasting
confidence: 99%
“…In fact, information on the crosstalk between melatonin and clock genes in pathological situations is very scarce; the most detailed data have been obtained in breast cancer, having been found that melatonin, via activation of MT1, represses the transcriptional activity of RORα to suppress BMAL1 promoter activity ( Xiang et al, 2012 ). Regulation of clock through changes in CLOCK phosphorylation which could modify the transactivation activity of CLOCK-BMAL1 ( Luciano et al, 2018 ) is another interesting possibility worthy to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AKT has also been found to act on the molecular clock, lengthening the circadian period [148]. AKT-driven phosphorylation of CLOCK directs it for nuclear translocation, affecting the expression of downstream metabolic genes [149]. A number of metabolites display circadian oscillation [150][151][152] and important regulators of metabolism, such as Ras, c-Myc, nuclear hormone receptors and p53 are also associated with circadian rhythms (reviewed in [142,153,154]).…”
Section: Circadian Control Of Metabolismmentioning
confidence: 99%